Performance of Civil Servants in the Bureau of Government and Community Welfare, Regional Secretariat of Bengkulu Province - Amanda Mutiara Zahra; Evi Lorita; Harius Eko Saputra (Social Sciences Journal, 2026)
This study aims to analyze the performance of civil servants at the Bureau of Government and Community Welfare, Regional Secretariat of Bengkulu Province, using Kompri’s (2020) performance indicators, which include input, process, output, outcome, and impact. The research employs a descriptive qualitative method, with data collected through in-depth interviews with four informants representing both structural and functional positions. The results show that the overall performance of civil servants is categorized as good. Employees demonstrate adequate quality and quantity of work, completing tasks in accordance with SOPs and meeting targets with some variation across roles. Timeliness is generally maintained, with some employees completing tasks beyond regular hours. Efficiency is reflected in the use of digital tools and work coordination, although limited facilities pose challenges. Creativity emerges in employees’ ability to adapt to logistical constraints and support digital bureaucratic processes. Strong responsibility is also evident through consistent task completion and inter-unit coordination. These findings indicate that employee performance is strengthened by structured procedures, technological adaptation, and commitment, although improvements in supporting facilities are still needed to optimize productivity.